Evaluation of HOTS-Based questions in Islamic cultural history at Insan Cendekia Boarding School Sukoharjo - Khairunamira, Fathya; Rohimah, Siti (Asatiza: Jurnal Pendidikan, 2025)
This study evaluates the quality of Higher Order Thinking Skills (HOTS) questions in the Islamic Cultural History (SKI) subject for grade VIII students at SMP Insan Cendekia Boarding School Sukoharjo during the 2023–2024 academic year. Despite the Ministry of Religious Affairs’ initiative to promote HOTS-based assessments, their implementation in SKI examinations remains inconsistent. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. The interviews explored teachers' challenges in developing HOTS questions, including their understanding of HOTS, prior experience in question formulation, and implementation difficulties. Data were analyzed through data reduction, data display, and conclusion drawing. An analysis of 45 SKI exam questions revealed that none met HOTS criteria, with 39 classified under recall (C1) and 6 under comprehension (C2), while none reached application (C3) or higher. These findings indicate that the SKI exam does not align with HOTS development criteria, as it predominantly consists of lower-order thinking questions. Consequently, students rely on rote memorization rather than developing critical, analytical, and evaluative thinking skills. This study highlights the need to revise assessment frameworks and enhance teachers’ capacity in designing HOTS-based questions to foster deeper and more contextualized learning in Islamic history.